Development of CT Using Need Assessment and Gamification: A Systematic Review - Aroonsiwagool, Athit; Tuntiwongwanich, Somkiat (My University, 2021)
This study originates from the content synthesis of studies on computational thinking, need assessment, gamification, and computational thinking with coding from Thai and international scholarly articles published in accredited databases. Then, the synthesis results were integrated into the development of computational thinking through gamification and programming knowledge to improve the efficacy of computational learning. The process commenced with an analysis of the learners' needs obtained through the questionnaires concerning computational thinking. Data analysis illuminated the learners' levels of computational thinking as well as a fundamental understanding of what the learners need to be taught or what areas of skills each learner. With regards to this, conventional teaching approaches may not serve best to transmit the relevant knowledge which may subsequently induce unfavorable attitudes toward computational thinking. With the data elicited through the need assessment, instructors will have a clear direction as to how the pedagogical process should be designed to directly address the needs in each of the computational thinking components. In general, each component of them is rather complex, so the researcher incorporated gamification theory-based learning defined by its enjoyable game mechanisms and challenging nature which makes the coding lesson fun with block programming enabling learners to proficiently grasp the concept of computational thinking.
Keywords: computational thinking; computational thinking with coding; gamification; need assessment